Liposomal nanoparticles based on steroids and isoprenoids for nonviral gene delivery. (2nd November 2021) - Maiti, Bappa; Bhattacharya, Santanu
Abstract: Natural lipid molecules are an essential part of life as they constitute the membrane of cells and organelle. In most of these cases, the hydrophobicity of natural lipids is contributed by alkyl chains. Although natural lipids with a nonfatty acid hydrophobic backbone are quite rare, steroids and isoprenoids have been strong candidates as part of a lipid. Over the years, these natural molecules (steroid and isoprenoids) have been used to make either lipid‐based nanoparticle or functionalize in such a way that it could form nano assembly alone for therapeutic delivery. Here we mainly focus on the synthetic functionalized version of these natural molecules which forms cationic liposomal nanoparticles (LipoNPs). These cationic LipoNPs were further used to deliver various negatively charged genetic materials in the form of pDNA, siRNA, mRNA (nucleic acids), and so on. This article is categorized under: Biology‐Inspired Nanomaterials > Lipid‐Based Structures Abstract : Liposomal nanoparticles (LipoNPs) for gene delivery.